Paraclaravis, a new genus for the Purple-winged and Maroon-chested Ground-doves (Aves: Columbidae) - Sangster, George; Sweet, Andrew D.; Johnson, Kevin P. (Zootaxa, 2018)
Previous molecular phylogenetic analyses and new analyses reported here demonstrate that the genus Claravis is not monophyletic and comprises two lineages, one with the species pretiosa Ferrari-Pérez, 1886 (Blue Ground-dove), and the other with two species: geoffroyi Temminck, 1811 (Purple-winged Ground-dove) and mondetoura Bonaparte, 1856 (Maroon-chested Ground-dove). Because the generic name Claravis is typified by C. pretiosa (Ferrari-Pérez, 1886), a new genus, Paraclaravis gen. nov., is described for geoffroyi Temminck, 1811 and mondetoura Bonaparte, 1856.